COOKIES WITH NUTRITIONAL VALUE ADDED - López R., Luz (2002)
Considering the deficiency of proteins in the Peruvian residerifs diet, their alimentary habits and preferences in the ingesta of foods for quick consumption for the dynamism of the daily activities, one worked with the addition of proteins of high biological value in formulations of crakers. For this reason we prepare the flour, using as matter prevails to the hake that was selected applying the chart of evaluation organoléptica of Whittfogel, the procedures of obtaining of the hake flours they were compared, in those that optionally the pH was adjusted. The comparison of the elaborated fish flour was carried out with the standard flour of wheat. Tests were made with substitutions of 5, 10 and 15% of flour of having fished by wheat flour in the patron formulation of cookies and the acceptability of the product was evaluated making texture tests, color, scent and satisfaction of the products. He/she was that 17% of the panelists detected the incorporation of fish flour in the prepared mass. The tests were carried out to small scale and in the sensorial analyses not trained judges participated.